Unraveling the non-linear relationship between seasonal deformation and permafrost active layer thickness - Tian Chang; Yonghong Yi; Huiru Jiang; Rongxing Li; Ping Lu; Lin Liu; Lingxiao Wang; Lin Zhao; Simon Zwieback; Jingyi Zhao (npj Climate and Atmospheric Science)
Abstract Accurate estimate of active layer thickness (ALT) is crucial for understanding permafrost and ecosystem responses to climate change. Interferometric Synthetic Aperture SAR (InSAR) technology can detect active layer freeze-thaw induced surface deformation with high accuracy, facilitating more accurate ALT estimation at the regional scale. Previous studies revealed a positive relationship between ALT and seasonal deformation in poorly drained Arctic soils. However, whether such relationship still holds in arid permafrost regions such as the Qinghai-Tibet Plateau (QTP) remains uncertain. Through synthesizing extensive field observations and remote sensing data, we find an overall negative correlation (r = -0.53, p < 0.01) between ALT and seasonal deformation in QTP, which tends to become more negative with sparser vegetation and drier soils, in contrast to the Arctic. After normalizing the climatic effect on ALT, we observe a decreasing sensitivity of seasonal deformation to active-layer changes with drier soils. Our study reveals a non-linear relationship between ALT and seasonal deformation across different permafrost regions, which helps to inform future development of InSAR-based permafrost applications.